Relevansi Restorative Justice dalam Penyelesaian Perkara Pemalsuan Uang yang Dilakukan oleh Anak - Najwa Deisya Mayla; Fristia Berdian Tamza; Diah Gustiniati Maulani; Dona Raisa Monica; Refi Meidiantama (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research aims to analyze the relevance of applying restorative justice in resolving counterfeiting cases committed by children, by examining the normative, juridical, and practical aspects within Indonesia’s juvenile criminal justice system. The background of this study arises from the dilemma between protecting the rights of children as offenders and the state’s obligation to maintain economic stability and public trust in the national currency. The research method employed is juridical-descriptive with a normative approach,. The implementation of restorative justice can still safeguard public interests, provided it involves relevant institutions such as Bank Indonesia and produces measurable recovery agreements. Thus, restorative justice serves as an alternative approach that balances child protection and legal certainty, while also contributing to the prevention of counterfeit money circulation in society.